Uji performa dan konsumsi bahan bakar menggunakan kombinasi bioetanol Manihot Utilissima - Dani Hari Tunggal Prasetiyo; Djoko Wahyudi (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2023)
Advances in technology have an impact on increasing the population of vehicles as a means of transportation. Currently the vehicle's work system to produce energy still uses internal combustion. The fuel used as an energy source is still dominated by fuel oil. If exploitation continues without using alternative fuels, it is predicted that there will be a fuel crisis in the future. Therefore, efforts are needed to conserve fossil fuels. One way to do this is by adding bioethanol. This research was conducted by adding bioethanol from cassava to gasoline type fuel with an octane rating of 92. This study aims to determine the performance and fuel consumption. Tests varied the fuel composition by 5%, 10%, 15%, 20% with engine speed of 1,000 to 8,000 rpm. The test results show that the composition of Pertamax 80% with 20% bioethanol produces the highest power and torque of 8.87 hp and 8.32 N.m, but for the lowest fuel consumption the fuel composition is Pertamax turbo 100% with a fuel consumption value of 38.8 ml/min.